Unveiling the Power of Tunable RXZnCH2I Carbenoids for the Cyclopropanation of Olefins - Feng, Xiangqing; Du, Haifeng (Synthesis)
Cyclopropanes are both valuable building blocks in synthetic chemistry and important functional moieties existing in natural products and biologically active molecules. The Simmons-Smith cyclopropanation has become a very useful and reliable method for the synthesis of cyclopropanes from olefins. Aiming at the development of tunable and highly reactive zinc carbenoids, Shi and coworkers put forward an effective strategy for the generation of zinc carbenoids RXZnCH2I by reacting RXH with an appropriate organozinc reagent, which allows tuning the reactivity of RXZnCH2I reagents simply by changing the modifier RXH. This type of carbenoid reagents was known as Shi carbenoid or reagent and found to be highly effective for each type of olefins, which attracts intensive attention and results in numerous successful applications in the synthesis of complex molecules as well as important cyclopropane building blocks. Significantly, the asymmetric Simmons-Smith cyclopropanation of unfunctionalized olefines has also been achieved using a chiral modifier.